Collaborative Learning Activity Utilizing Evidence-Based Medicine to Improve Medical Student Learning of the Lifestyle Management of Obesity - Magdalena Pasarica; David M. Harris; Judith Simms-Cendan; A. Laurel Gorman (Association of American Medical Colleges, 2016)
Abstract Introduction Innovative and effective curricula for medical students and physicians are needed to increase knowledge and confidence for instructing patients on lifestyle management of diseases. We developed an active collaborative session that integrates evidence‐based medicine (EBM), clinical decision-making, nutrition, exercise, and personalized patient care for the instruction of lifestyle management of obesity in the preclinical medical curriculum. Methods Before the session, learners critically appraised an EBM article (meta‐analysis of commercial weight-loss programs' efficacy). In class, there was an EBM discussion assessed and facilitated by multiple-choice questions, followed by a collaborative activity where learners solved a clinical scenario of a patient who wants to use a commercial weight-loss program. Each small group was assigned to a different program but given the same clinical scenario. The objectives of the session were to identify and interpret EBM/non‐EBM resources in order to describe the components, advantages, and disadvantages of the weight-loss programs, make a personalized clinical recommendation, and present it to the class. Results Generating debate and fostering engagement, the session was perceived as a positive learning experience by the learners. By accomplishing the learning objectives, the participants became well versed in various weight-loss programs. Discussion Our results suggest that learners developed interpretation and knowledge integration skills, which may increase their comfort in discussing the lifestyle management of obesity and other diseases. This activity is designed to be implemented at other institutions seeking to integrate active collaborative learning of nutrition, exercise, and clinical decision-making during preclinical and clinical medical education and clinical practice.